(untitled) (Journal of the College of Basic Education, 2022)
The individual who has a high ability to confront is the person who can get rid of his suffering by abandoning the wrong and irrational thinking patterns.The coping methods reflect the person’s ability to effectively agree and the degree of his tolerance for high pressure. Therefore, the distinguishing feature of the coping methods is to enhance the coping strategies and preserve the coping resources available to use them efficiently when needed.Although self-efficacy is a mediator between knowledge and reason, because the beliefs that individuals form about their abilities and their expectations affect the ways in which they act, individuals differ among themselves in their choice of tasks that they will perform in terms of their competence and capabilities.